2017
DOI: 10.1007/s12035-017-0781-2
|View full text |Cite
|
Sign up to set email alerts
|

AZI23’UTR Is a New SLC6A3 Downregulator Associated with an Epistatic Protection Against Substance Use Disorders

Abstract: Regulated activity of SLC6A3, which encodes the human dopamine transporter (DAT), contributes to diseases such as substance abuse disorders (SUDs); however, the exact transcription mechanism remains poorly understood. Here, we used a common genetic variant of the gene, intron 1 DNP1B sequence, as bait to screen and clone a new transcriptional activity, 3'UTR, for SLC6A3.3'UTR is a 3' untranslated region (3'UTR) of the human 5-Azacytidine Induced 2 gene (AZI2) but appeared to be transcribed independently of AZI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(56 citation statements)
references
References 41 publications
0
56
0
Order By: Relevance
“…Specifically data from four SUD [12] cohorts were obtained from the three datasets: Collaborative Study on the Genetics of Alcoholism (COGA, dbGaP accession#: phs000125.v1.p1), Study of Addiction: Genetics and Environment (SAGE, polysubstance abuse but mainly with cigarette smoking, dbGaP accession#: phs000092.v1.p1), and the Australian twin-family study of alcohol use disorder (OZALC, dbGaP accession#: phs000181.v1.p1). After COGA data quality control (QC), data from the US Caucasians of European (EA) descent and African Americans (AA) were split into these 2 separate ethnic cohorts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically data from four SUD [12] cohorts were obtained from the three datasets: Collaborative Study on the Genetics of Alcoholism (COGA, dbGaP accession#: phs000125.v1.p1), Study of Addiction: Genetics and Environment (SAGE, polysubstance abuse but mainly with cigarette smoking, dbGaP accession#: phs000092.v1.p1), and the Australian twin-family study of alcohol use disorder (OZALC, dbGaP accession#: phs000181.v1.p1). After COGA data quality control (QC), data from the US Caucasians of European (EA) descent and African Americans (AA) were split into these 2 separate ethnic cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…Determine whether these neuropsychiatric disorders have common risks in DA-associated genes, including DA synthesis (2 genes), metabolism (2 genes), receptors (DRs, 5 genes), monoamine transporters (5 genes), an uptake modulator (alpha-synuclein: SNCA), and transcription factors (7 genes) [11,12].…”
Section: Aimmentioning
confidence: 99%
“…The Azi2 3'UTR on exon 8 that we amplified using qRT-PCR is homologous to the 3'UTR amplified in the rat alcohol model (Liu et al, 2018) and is only present in two of the four full-length Azi2 transcripts, ENSMUST0000044454.11 and ENSMUST00000133580.7.…”
Section: Qrt-pcrmentioning
confidence: 98%
“…One possible mechanism by which Azi2 could influence the response to methamphetamine was proposed by another group after the publication of Parker et al (2016) (20). Liu et al (2018) identified the second half of 3' UTR of Azi2 mRNA ( AZI2 3'UTR) as a regulator of Slc6a3 (Liu et al, 2018), which encodes the dopamine transporter (DAT), a critical regulator of the neurotransmitter dopamine concentrations in the synaptic cleft. Importantly, DAT is the molecular target of methamphetamine (28), providing a plausible mechanism by which Azi2 might influence sensitivity to methamphetamine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation